Simulation-Based Prediction of Office Buildings Energy Performance Under RCP Scenarios Across All U.S. Climate Zones - Sepideh Niknia; Mehdi Ghiai (Architecture)
Buildings account for a significant portion of global energy consumption and are increasingly vulnerable to the adverse effects of climate change, including rising greenhouse gas emissions and shifting weather patterns. These disruptions significantly impact energy demand, necessitating proactive measures to ensure buildings remain functional, sustainable, and energy efficient. This study offers a novel contribution by systematically comparing the energy performance of office building prototypes using a simulation-based method across all U.S. climate zones under projected Representative Concentration Pathways (RCPs) 4.5 (moderate emissions) and 8.5 (high emissions) for the years 2050 and 2080. This multi-scale and multi-scenario simulation provides a nationally comprehensive view of how building size and climate conditions interact to influence vulnerability to future energy demand shifts. The findings reveal that medium-sized office buildings are the most vulnerable to climate change, with an average Energy Unit Intensity (EUI) increase of 12.5% by 2080 under RCP 8.5, compared to a 7.4% rise for large office buildings and a slight decline of 2.5% for small office buildings. Hot and humid cities such as Miami, FL, experience the highest increases, with EUI projected to rise by 21.2% for medium offices, while colder regions like Fairbanks, AK, show reductions of up to 18.2% due to decreasing heating demands. These results underscore the urgent need for climate-compatible building design strategies, particularly in high-risk areas. As climate change intensifies, integrating resilience-focused policies will safeguard energy systems and ensure long-term occupant comfort.